Asymmetric synthesis of fluorinated derivatives of aromatic and γ-branched amino acids via a chiral Ni(II) complex - Maurizio Iannuzzi; Thomas Hohmann; Michael Dyrks; Kilian Haoues; Katarzyna Salamon-Krokosz; Beate Koksch (Beilstein Journal of Organic Chemistry)
Fluorinated amino acids are essential building blocks in the spheres of protein engineering and medicinal chemistry. In the last decades, a large number of different synthetic strategies have been developed to produce a large variety of fluorinated amino acids. Still, obtaining fluorinated amino acids in great quantities can be challenging, or the corresponding pathways are heavily time-consuming and synthetically challenging. In this context, chiral Ni(II) complexes can be powerful tools to obtain tailor‑made non‑canonical amino acids. In this work, we wanted to take advantage of this strategy and extend the range of this method to include additional fluorinated amino acids. We synthesized two fluorinated analogs of phenylalanine, which are still unexplored in the context of peptide and protein chemistry. Furthermore, both diastereomers of trifluoroleucine were synthesized, demonstrating that the described strategy can also be applied to synthesize enantio‑ and diastereomerically pure γ‑branched fluorinated amino acids. This work further underlines the importance of chiral Ni(II) complexes in the synthesis of fluorinated amino acids.